The Balanced Budget: Reply - Burkhead, Jesse (Quarterly Journal of Economics, 1955)
Journal Article The Balanced Budget: Reply Get access Jesse Burkhead Jesse Burkhead Syracuse University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 69, Issue 1, February 1955, Pages 155–156, https://doi.org/10.2307/1884857 Published: 01 February 1955